Comparative analysis of communication strategies in promoting csr programs: Pertamina vs Petronas - Syafrizaldi; Iswahyu Pranawukir; Robbi Rahim; Mohamad Sudi; Slamet Riyadi (Jurnal Studi Komunikasi, 2023)
This research contrasts the digital strategic communication approaches employed by Pertamina (Indonesia) and Petronas (Malaysia), two prominent Southeast Asian oil and gas corporations, in disseminating their Corporate Social Responsibility (CSR) projects. As environmental concerns and climate change intensify, these companies have advanced significantly in sustainable development. Corporate social responsibility (CSR) is highly valued in modern society, particularly for oil and gas enterprises catering to regional energy demands. While Pertamina and Petronas fulfil national roles, they also confront global sustainability challenges. The methodology involves analysing the Instagram profiles of @pertamina and @petronas. The study employs qualitative content analysis to scrutinise visual rhetoric, engagement metrics, message framing, the frequency of CSR posts, and audience responses, including likes, comments, and shares. The results indicate distinct approaches by each company in utilising Instagram for their sustainability campaigns. Pertamina adopts straightforward communication techniques to elucidate its CSR initiatives, while Petronas employs storytelling to link business activities with societal issues. These insights could influence the digital communication strategies of other firms in CSR efforts. The study suggests that cultural relevance and societal significance can enhance stakeholder involvement on Instagram. It concludes that proficient digital strategic communications can mould public perceptions of a business's commitment to sustainability.